The purpose of business: contemporary perspectives from different walks of life - Erisman, Albert; Gautschi, David A. (Palgrave Macmillan, 2015)
Preface: the consortium on the purpose of business / Al Erisman and David Gautschi -- The business school : serving mammon or the university / David Gautschi and Jonathan Story -- Dean panel response : "What is the purpose of business?" / Philippe Naert, Indira Parikh, Jeff Van Duzer, and Denise Daniels -- Why focus on the maximization of shareholder value must fail / Al Erisman -- A practitioner perspective : purpose and practice of business (an interview with Jack Vanhartesvelt) / Al Erisman -- Global assessment / Jonathan Story -- God and the market : four settings in the Eastern Mediterranean / Patrick J. Ryan, S.J -- Business and religion : religious perspectives on business from Buddhism, Christianity, Islam, and Judaism ( a collection of interviews and essays with Seamus Phan, David W. Miller, Rabbi Daniel Lapin, Dr. Muhammad Arif Zakaullah) / Al Erisman -- Business and energy / Jonathan Story -- Behavioral economics and business / Hersh Shefrin -- Business and the brain (an inteview with John Medina) / Al Erisman -- Business and global politics / Adriana and Fabián Fábrega -- Business and the arts / Indira Parikh -- Concluding remarks / Al Erisman and David Gautschi --